Association between intensive care unit delirium and delusional memory after critical care in mechanically ventilated patients - Yasuyo Yoshino; Takeshi Unoki; Hideaki Sakuramoto; Akira Ouchi; Haruhiko Hoshino; Yujiro Matsuishi; Taro Mizutani (Wiley, 2021)
Abstract Aim To determine the relationship between the delirium of patients with mechanical ventilation during intensive care unit (ICU) stay and delusional memory after ICU discharge. Design Prospective cohort study. Methods Delirium in adult patients who received mechanical ventilation for more than 24 hr was assessed twice daily using the Confusion Assessment Method for the ICU. Delusional memories were evaluated using the ICU Memory Tool 5-10 days after ICU discharge. The associations between the presence of delirium during the ICU stay and delusional memories were evaluated. Results Of 60 enrolled patients, 62% had delirium during their ICU stay, and 68% experienced delusional memories 5-10 days after discharge. Delirium during ICU stay was an independent factor to experience delusional memories following discharge. Preventing delirium during ICU stay might reduce delusional memory. We recommend that patients with delirium during their ICU stay should be carefully followed up after discharge from the ICU.